EFEKTIVITAS PENGGUNAAN MEDIA CORONG BERHITUNG DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN OPERASI BILANGAN DI KELAS III MI AL-MUNAWWARAH - Nursam Nursam; Thalib Thalib; Arfan Hakim (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
This article deals with “The Effectiveness of Using the Cut-Out Funnel Media on Students' Learning Outcomes on the Subject of Number Operations in Class III MI Al-Munawwarah Kec. Sarjo Kab. Pasangkayu ". The main problem in this thesis is how to effectively use the counting funnel media so that it can improve student learning outcomes on multiplication material in class III MI Al-Munawwarah Sarjo. The purpose of this study was to obtain a description of the effectiveness of using counting funnel media in an effort to improve student learning outcomes on the multiplication material in class III MI Al-Munawwara Sarjo. This type of research is Classroom Action Research (PTK) using qualitative and quantitative approaches. This classroom action research model is a cyclical model consisting of cycle I and cycle II. The subjects of this study consisted of 24 students in class III with data collection techniques including: observation, interviews, field notes, pre-action tests, pre-action tests, and post-action tests. The learning outcomes of students showed that through action in the first cycle there was an increase in the percentage where the first cycle was 54.16% and the second cycle was 95.83% with the percentage difference between the two cycles of 41.67% while learning about the activities of the teacher (researcher) experienced the increase with the percentage acquisition of cycle I is 77.5% and cycle II is 100% so that the selection between the two cycles is 22.5% while the activity of students has increased with the percentage in cycle I, namely 68.75%, cycle II, namely 100% the cycle experienced a difference of 31.25%. Regarding the percentage increase in learning outcomes and the learning process, it shows that the funnel-counting media is effectively used in mathematics multiplication subjects. Thus it can be concluded that the use of counting funnel media is effective as seen from the observations of teacher activity and student activity as well as increased learning outcomes. Keywords : Effectiveness, Cut-Out Funnel Media, learning outcomes